Multicore DSP : from algorithms to real-time implementation on the TMS320C66x SoC - Dahnoun, Naim (John Wiley & Sons, 2018)
Offers special coverage of the fundamentals of multicore DSP for implementation on the TMS320C66xx SoC. This unique book provides readers with an understanding of the TMS320C66xx SoC as well as its constraints.